Correlation between ovarian chocolate cyst and serum carbohydrate antigen 125 level and the effect of ultrasound‐guided interventional sclerotherapy on serum carbohydrate antigen 125 level. Issue 1 (27th August 2014) - Wang, Si‐Ming; Cai, Huai‐Qiu; Dong, Xiao‐Qiu; Fan, Qiu‐Lan; Wang, Lu‐Lu; Shao, Xiao‐Hui; Zhang, Li‐Wei
Abstract Aim This study was to investigate the correlation between ovarian chocolate cysts and serum carbohydrate antigen (CA)‐125 levels and to demonstrate the effect of ultrasound‐guided interventional sclerotherapy (UGIS) on serum CA‐125 levels. Methods Based on the serum CA‐125 level, as determined by chemiluminescence detection prior to UGIS, 105 patients with ovarian chocolate cysts were divided into the normal group (CA‐125 ≤ 35 U/mL, 45 patients) and the abnormal group (35 U/mL < CA‐125 ≤ 200 U/mL, 60 patients). There were six clinical indicators including age, disease duration, dysmenorrhea history, child‐bearing history, abortion history and surgical history. The ultrasonography characteristics were cyst diameter, cyst wall thickness and the side on which the cyst occurred. The correlations between serum CA‐125 levels pretreatment and the clinical indicators and ultrasonography characteristics was analyzed. The serum CA‐125 levels pretreatment, 3 months post‐treatment and 6 months post‐treatment were compared. Results The pretreatment serum CA‐125 levels of the 105 patients positively correlated with disease duration (r = 0.3932, P = 0.0040), dysmenorrhea history (r = 0.2351, P = 0.0111), cyst diameter (r = 0.3415, P < 0.0001) and cyst wall thickness (r = 0.4263, P < 0.0001). Compared with the pretreatment level, the mean serum CA‐125 level in the abnormal group at 3 months post‐treatment was significantly lower (P < 0.01), and at 6 months post‐treatment, the mean serum CA‐125 level had decreased to a normal level (P < 0.01). Conclusion UGIS significantly decreased abnormal serum CA‐125 levels in patients with ovarian chocolate cysts.